Structural changes in V2O5-P2O5 glasses: non-constant force field molecular dynamics and IR spectroscopy - A. A. Raskovalov; N. S. Saetova; I. S. Popov (Chimica Techno Acta)
Quasi-binary phosphate-vanadate glasses have been studied by both IR spectroscopy and a novel method of molecular dynamics with a non-constant force field. This method is used for the self-assembly of structural models of glasses. The obtained models and the glass network structure are analyzed quantitatively using element distribution by the number of R–O–R bonds (R is phosphorous or vanadium) and 4-, 6-, and 8-membered cycles. The bends on the concentration dependences of atoms distribution in the second coordination sphere agree well with changing the shape of IR spectra. Based on the cycle analysis, the formation of cycles is shown to be more characteristic for vanadate fragments that can form 4-membered cycles, which, according to Zachariasen’s rule, negatively affects glass-forming ability.